2002
DOI: 10.5194/aab-45-13-2002
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic haplotypes at the bovine <i>CSN1S1</i> locus

Abstract: SummaryA new alternative genotyping method based on PCR-SSCP was developed for direct differentiation of the CSN1S1 alleles B and C in the coding region. In addition a PCR-RFLP test based on a MaeIII restriction site in the promoter region of CSN1S1, reported in the literature as an alternative test for the differentiation of CSN1S1*B and C was used and the alleles named b and c. Genotyping of 649 animals belonging to 17 European and Turkish cattle breeds showed differences in occurrence and frequency of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…However, it can be concluded that despite the close physical linkage of the genes, recombination seems to be relatively frequent within the casein locus. This confirms the observations already described by [19] and [39].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it can be concluded that despite the close physical linkage of the genes, recombination seems to be relatively frequent within the casein locus. This confirms the observations already described by [19] and [39].…”
Section: Discussionsupporting
confidence: 93%
“…The α s1 -casein gene was typed for a MaeIII polymorphism in the promoter region (CSN1S1prom) by PCR-RFLP according to the protocol of [20] and for a polymorphism in exon 17 (CSN1S1) with PCR-SSCP which differentiates CSN1S1*B from CSN1S1*C [19]. Within the α s2 -casein gene, the nucleotide exchange differentiating CSN1S2*A and D was analysed by ACRS [36].…”
Section: Genotyping Of Casein Polymorphismsmentioning
confidence: 99%
“…All loci were in Hardy–Weinberg equilibrium. Of the four alleles detected at the CSN1S1 locus, three were present in the Reggiana, with the predominance of CSN1S1*B and a rather high frequency (0.244) of CSN1S1*C compared with Italian Holstein and Italian Brown and more generally to most taurine breeds ( Baker and Manwell 1980; Grosclaude 1988; Jann et al. 2002).…”
Section: Resultsmentioning
confidence: 98%
“…All loci were in Hardy-Weinberg equilibrium. Of the four alleles detected at the CSN1S1 locus, three were present in the Reggiana, with the predominance of CSN1S1*B and a rather high frequency (0.244) of CSN1S1*C compared with Italian Holstein and Italian Brown and more generally to most taurine breeds (Baker and Manwell 1980; Grosclaude 1988;Jann et al 2002). In Nordic cattle Lien et al (1999) identified an allele frequency gradient with lower frequency of CSN1S1*B in native breeds, and loss of CSN1S1*C in highly selected dairy cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Basic knowledge related to the biology of lactoprotein gene expression is therefore of crucial importance for the advancement of milk production. Identification of important regulatory elements and allele specific polymorphisms within the promoter regions of the bovine casein genes (JANN et al, 2002) would provide an interesting basis for the marker assisted selection in dairy cattle. Accumulation of genomic data during the last two decades enabled more focused research of molecular mechanisms governing casein synthesis in the mammary gland.…”
Section: Introductionmentioning
confidence: 99%